Science Management Challenges Facing in the Industrial Revolution Era 4.0 - Rezi Muhamad Taufik Permana (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Science Management is now a challenge in facing the industrial era 4.0 where organizations and the industrial world are currently experiencing a more adaptive approach in viewing organizational theories in the field of management. The purpose of this research is to find out how big the impact of technological developments is on the development of science, especially management. This research was conducted with a qualitative descriptive approach by looking at the theories of management science with a case approach of the industrial era 4.0. This study uses secondary data contained in books, white papers, journals, articles which is the basis for a literature review. The results show that the role of organizational members, especially stakeholders, is required to study and understand all management theories produced by various streams and concepts or approaches that are most suitable for dealing with simple and complex problems and, this approach describes the current conditions. conditions and management positions in the future.